Islam in the Midst of AI (Artificial Intelligence) Struggles: Between Opportunities and Threats - Khoirunisa, Ana; Rohman, Fathur; Azizah, Hilda Aulya; Ardianti, Devi; Maghfiroh, Arinta Lailatul; Noor, Aditya Muhammad (Universitas Muhammadiyah Surakarta, 2023)
Islam is a religion that accepts all forms of technological progress, including advances in artificial intelligence. However, in the development of technology, Muslims are required to adapt to anticipate the negative or positive impacts that exist. The purpose of this study is to find out the opportunities and threats that accompany the emergence of AI (Artificial Intelligence) so that AI (Artificial Intelligence) can be used in harmony with the Islamic religion. The qualitative method was chosen in this study, by collecting secondary data which was then analyzed to answer all questions. The results of the research show that if Artificial Intelligence is developed and implemented properly, it will be very helpful for the needs of Muslims. But there are also threats including; prone to be misused to instill the values of apostasy, radicalization and terrorism. The use of Artificial Intelligence in harmony with the Islamic religion, must pay attention to ethical and moral principles in the development and application of Artificial Intelligence.